ANALISIS BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP EKSPOR CENGKEH HARMONIZED SYSTEM (HS) 0907 INDONESIA KE ARAB SAUDI - Evi Fortuna Sukiran Putri; Niniek Imaningsih (Universitas Nias Raya, 2026)
Indonesia is the largest clove producer in the world and one of the major exporters after Madagascar. Cloves grow well in tropical regions like Indonesia and play an important role in the national economy. This study uses secondary data from 1998 to 2023 obtained from the World Bank, TradeMap, FAOSTAT, and the Directorate General of Plantations, Ministry of Agriculture of Indonesia. The study aims to analyze the factors influencing Indonesia’s clove exports, classified under the Harmonized System (HS) code 0907, to the Saudi Arabian market. The method employed is a secondary time series analysis using multiple linear regression at a 5% significance level. The results indicate that international prices have a significant negative effect, while clove production has a significant positive effect on Indonesia’s clove exports to Saudi Arabia. However, Saudi Arabia’s GDP does not show a significant effect on exports to the country, nor does the Rupiah-to-USD exchange rate significantly influence clove exports to Saudi Arabia.